Risk mitigation solution for infill drilling and well completion in Lower Miocene sediments in late reservoir life and in pressure and temperature depleted zones - Pham Van Hieu; Ta Van Thinh (Petrovietnam Journal, 2019)
The article evaluates the condition of well’s problems and accidents during drilling at Vietsovpetro Joint Venture and arising problems when drilling in late reservoir life. The effects of well and pore pressure and temprature depletion on the in-situ stress, wellbore stability, and mud loss are investigated. The efficiency of solutions for curing mud losses during infill drilling in the Lower Miocene sediments of the Cuu Long basin is also analysed. Based on that, the authors give a series of recommendations to ensure safe well construction through the pressure and temperature depleted zones.